ENGLISH SPEAKING ANXIETY AMONG INDONESIAN JUNIOR HIGH SCHOOL LEARNERS: IN SEARCH OF CAUSES AND SOLUTIONS - Arini Nurul Hidayati; Fuad Abdullah; Agis Andriani; Dewi Rosmala; Novi Nurvianti (English Education Department, 2022)
In the last few decades, foreign language speaking anxiety (hereafter, FLSA) has been a debatable investigative issue among linguists and TESOL practitioners. One of the most salient factors is it generates an incapacitating impact for speakers to communicate orally in English as a foreign language. However, delving learning activities as a cause of FLSA and its solutions, notably in Indonesian secondary school level remains scarce. To fill the void, this study scrutinized the specific learning activities causing learners’ FLSA in the classroom and the solutions to resolve them. Three junior high school learners were recruited as the participants. The data were collected through semi-structured interviews and analyzed thematically (Braun & Clarke, 2006). On the one hand, the findings outlined that the students suffered from FLSA when they engaged in questions and answer session of the classroom English language learning activities and speaking performance activities. On the other hand, the solutions of such FLSA encompassed focusing on the learning process and ignoring the disruptive behaviour of their classmates. Pedagogically, creating a less anxious atmosphere of learning English speaking practices enables students to successfully acquire English language skills (e.g., speaking) and adapt to appropriate social and academic milieu.